Znaczenie pozycji aniołów w grobie Jezusa w J 20,12 - Kubiś, Adam (The Biblical Annals, 2016)
Compared with the Synoptics, the Johannine angels assume a particular and significant position inside Jesus’ tomb. The evangelist describes it precisely as one angel sitting at the place of Jesus’ head and another at the place of Jesus’ feet. Not all Johannine commentators pay attention to this detail, yet a comparison with the descriptions of the angels’ positions in the different synoptic narratives demonstrates that they all reflect original editorial work on the part of each the evangelist. Consequently, these accounts can – and indeed do – convey particular ideological or theological stances typical of each gospel writer, including John. With regard to John 20:12, the article surveys proposals advanced by several Johannine commentators, beginning with some very obvious and prosaic explanations and ending with the most probable meanings behind the particular posture of Johannine angels. According to a strictly archeological-historical explanation, the position of the Johannine angles is no more than an indication that Jesus’ burial place was not a tomb of kôkîm type. The article also presents allegorical interpretations, from St. Augustine to St. Thomas Aquinas; a religious-cultural exposition referring to the Egyptian goddesses Isis and Nephthys; a few very literal explanations accentuating the physical emptiness between the angels; and an intertextual exposition based on a targumic reading of Isaiah 6. At the end, as the most persuasive solution, the article proposes that the Johannine angels represent the cherubs of the Ark of the Covenant and the mercy seat. This intertextual and symbolic interpretation likewise explains Mary Magdalene’s lack of fear and astonishment in her interaction with supernatural beings.